Economic burden of inpatients with viral hepatitis B-related diseases and the influencing factors. Issue 4 (1st December 2013) - Zhang, Hua; Chao, Jianqian; Zhu, Liguo; Song, Long; Li, Xiyan; Liu, Pei
Abstract : Objective: The purpose of this study was to analyze the economic burden of inpatients with hepatitis B virus (HBV)-related diseases and the influencing factors so as to provide an effective basis for the development of health prevention and control strategies. Methods: The patients were selected by means of successive sampling in the period between August and December 2012 from those who were diagnosed with HBV-related diseases and hospitalized in county-level medical institutions of Jiangsu Province. One hundred ninety-six patients were studied, including 3 patients with acute HBV, 141 with chronic HBV, 18 with compensatory cirrhosis, 22 with decompensated cirrhosis, and 12 with liver cancer. This study adopted a questionnaire method to investigate and calculate the direct and indirect economic burden of the subjects according to disease economic burden theories and methods. Multiple linear stepwise regression was used for analysis of the influencing factors for economic burden of inpatients with HBV-related diseases. Results: The average economic burden for the 196 inpatients investigated was RMB 28, 971. The direct economic burden was RMB 19, 916 (68.7%), including direct medical costs (RMB 19, 087; 95.8%) and direct non-medical costs (RMB 829; 4.2%). The indirect economic burden was RMB 9055 (31.3%), including patient-related expenses (RMB 6348; 70.1%) and nursing expenses (RMB 2707; 29.9%). According to the multiple linear stepwise regression analysis results, the hospital stay, proportion of medicine, age, and disease type affected the economic burden of the patients ( P <0.05). Conclusion: Patients with HBV-related diseases undertake a heavy economic burden for hospitalization, especially the direct economic burden. Therefore, the inpatients' economic burden can be reduced by shortening the hospital stay, reducing the medical expenses reasonably, and delaying the progression of disease as far as possible according to medical standards.